Preparation method of TiSiBN interface coating on ceramic fiber surface

By preparing TiSiBN interface coating on the surface of ceramic fibers using chemical vapor deposition technology, the problem of existing BN interface coating being sensitive to oxygen and water vapor at high temperatures is solved, and the high performance performance of ceramic matrix composite materials in water-oxygen environments is achieved.

CN117024159BActive Publication Date: 2025-04-29AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311021476.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-04-29
Estimated Expiration
2043-08-14

AI Technical Summary

Technical Problem

The BN interface coating in existing ceramic matrix composite materials is sensitive to oxygen and water vapor at high temperatures, resulting in insufficient water oxygen resistance and unable to effectively solve this problem.

Method used

TiSiBN interface coating was prepared by chemical vapor deposition process on the surface of ceramic fibers, and TiCl4, SiCl4, BCl3 and NH3 were used as reaction precursors to form an interface coating with excellent oxidation resistance and water oxygen resistance characteristics.

Benefits of technology

It improves the service performance of ceramic matrix composites in water and oxygen environments, enhances the protection ability of ceramic fibers, maintains a high strength retention rate, and expands the application range of materials in actual use environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117024159B_ABST
    Figure CN117024159B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method of a TiSiBN interfacial coating on the surface of ceramic fibers, comprising the following steps: placing the ceramic fibers in a muffle furnace to remove the sizing agent, and putting the ceramic fibers after removing the sizing agent into a deposition furnace; starting the vacuum system to evacuate the deposition furnace, and simultaneously introducing argon into the deposition furnace, and then starting the heating system to heat; after the heating is completed, stopping the introduction of argon and reducing the vacuum degree; successively introducing four reaction gases of H2, NH3, BCl3 and TiCl4 into the deposition furnace, and then simultaneously introducing two reaction gases of TiCl4 and SiCl4 into the deposition furnace, and the reaction gases perform chemical vapor deposition on the surface of the ceramic fibers; after the chemical vapor deposition is completed, successively closing the gas channels of TiCl4, SiCl4, BCl3, NH3 and H2, and then introducing argon into the deposition furnace to normal pressure, and closing the heating system and the vacuum system, and a TiSiBN interfacial coating can be obtained on the surface of the ceramic fibers. The present invention improves the oxidation resistance and water and oxygen resistance of the interfacial coating by adding Ti and Si to BN.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of ceramic-based composite material interface coatings, and in particular relates to a method for preparing a TiSiBN interface coating on the surface of a ceramic fiber. Background Art

[0002] As we all know, ceramic-based composites have a series of excellent properties such as low density, high modulus, high strength, wear resistance, high temperature resistance, oxidation resistance and creep resistance. Therefore, ceramic-based composites can be used to prepare high-temperature components for aerospace to achieve lightweight structure, simplify cooling structure, reduce cooling gas consumption, and improve combustion efficiency.

[0003] Due to the great brittleness of ceramic-based materials, ceramic fibers and interfacial coatings are needed to improve the toughness of ceramic-based composites. Ceramic fibers have excellent properties such as low density, high strength, high modulus, high temperature resistance, corrosion resistance and oxidation resistance. They are mainly used as reinforcements for ceramic-based composites to enhance the toughness of high-temperature resistant ceramic-based composites. Ceramic fibers must maintain sufficient strength because once the cracks in the ceramic matrix propagate, the load must be transferred to the ceramic fibers. The pull-out effect of ceramic fibers is determined by the fiber strength, interphase structure and fiber surface state. In the preparation process of ceramic-based composites, each link will have different degrees of influence on the performance of ceramic fibers.

[0004] As a toughening phase of ceramic matrix composites, the interface coating can improve the toughness of ceramic matrix composites by transmitting cracks. The interface coating on the surface of ceramic fiber is an important component of stress transmission and toughness improvement during the fracture process of ceramic matrix composites. It can protect ceramic fibers from chemical erosion during the preparation of ceramic matrix composites and adjust the interface bonding force between fibers and matrix.

[0005] The interface coating on the surface of ceramic fiber is usually prepared by chemical vapor infiltration (CVI). By controlling the process parameters, the thickness and crystal structure of the interface coating can be adjusted. At present, the most typical interface types of ceramic matrix composites are pyrolytic carbon (PyC) and boron nitride (BN). The BN interface (oxidation starting temperature to 800℃) has better oxidation resistance than the PyC interface (oxidation starting temperature to 500℃). On the basis of achieving the debonding and slip behavior required by the interface material, the BN interface can improve the oxidation resistance of the material more than the PyC interface. Therefore, the BN interface is more suitable for ceramic matrix composites in high temperature oxidation environments. However, the BN interface coating is sensitive to oxygen and water vapor at high temperatures. The most effective solution is to dope certain elements in BN. There are many doping schemes in the prior art, but none of them can fundamentally solve the problem of low water and oxygen resistance of the BN interface coating. Therefore, it is necessary to develop a new preparation technology for the ceramic fiber surface interface coating so that the prepared interface coating has excellent oxidation resistance and water and oxygen resistance at the same time.

[0006] The invention patent with application publication number CN108892521A discloses a method for preparing a wave-transmitting ceramic-based composite material containing a silicon-boron-nitrogen interface, comprising the following steps: on the surface of a wave-transmitting ceramic fiber preform, chemical vapor deposition is performed using silane, boron trichloride and ammonia as precursors, hydrogen as a carrier, and argon as a diluent gas to obtain a fiber preform with an amorphous SiBNC coating, wherein the molar ratio of silane, boron trichloride, ammonia and hydrogen is 2-4:1-2:3-6:10; heat-treating the obtained fiber preform with an amorphous SiBNC coating to obtain a fiber preform with a SiBN wave-transmitting coating; placing the obtained fiber preform with a SiBN wave-transmitting coating in a borohydrazine precursor slurry for pressure impregnation, and then cracking it in a cracking furnace to obtain a wave-transmitting ceramic-based composite material containing a silicon-boron-ammonia interface. The interface coating in this technical solution is a BN interface, which is not resistant to water and oxygen. Although Si elements are added, the problem that the BN interface is sensitive to oxygen and water vapor at high temperatures cannot be solved. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a TiSiBN interface coating on the surface of a ceramic fiber, which comprises the following steps in order:

[0008] Step 1: Use a clamping tool to clamp the ceramic fiber and place it in a muffle furnace to remove the sizing agent;

[0009] Step 2: Place the ceramic fiber after the sizing agent is removed and the clamping tooling into the deposition chamber of the deposition furnace, and turn on the vacuum system to check the sealing of the deposition furnace;

[0010] Step 3: Turn on the vacuum system to evacuate the deposition furnace, and at the same time, introduce argon gas into the deposition furnace, and then turn on the heating system to heat it, and keep evacuating and introducing argon gas during the entire heating process;

[0011] Step 4: After the heating is completed, stop introducing argon gas and reduce the vacuum degree;

[0012] Step 5: Four reaction gases, H2, NH3, BCl3 and TiCl4, are introduced into the deposition furnace in sequence, and then two reaction gases, TiCl4 and SiCl4, are introduced into the deposition furnace at the same time, and the reaction gases are chemically vapor deposited on the surface of the ceramic fiber;

[0013] Step 6: After the chemical vapor deposition is completed, the gas channels of TiCl4, SiCl4, BCl3, NH3 and H2 are closed in turn, and then argon gas is introduced into the deposition furnace until the pressure in the deposition furnace reaches normal pressure. The heating system and the vacuum system are closed to obtain a TiSiBN interface coating on the surface of the ceramic fiber.

[0014] Preferably, in step one, the ceramic fiber is any one of carbon fiber, silicon carbide fiber, boron nitride fiber or silicon nitride fiber, and the type of the ceramic fiber is any one of ceramic fiber bundle, ceramic fiber plain fabric, ceramic fiber satin fabric, ceramic fiber 2.5D fabric or ceramic fiber 3D fabric.

[0015] In any of the above schemes, preferably, in step one, the process for removing the sizing agent from the ceramic fiber bundle, ceramic fiber plain fabric or ceramic fiber satin fabric is: first, the ceramic fiber bundle, ceramic fiber plain fabric or ceramic fiber satin fabric is placed in a muffle furnace, and then the temperature is increased to 250-400°C at a heating rate of 5-10°C / min, and the temperature is kept for 0.5-2h, and finally the furnace is cooled to room temperature; the process for removing the sizing agent from the ceramic fiber 2.5D fabric or ceramic fiber 3D fabric is: first, the ceramic fiber 2.5D fabric or ceramic fiber 3D fabric is placed in a muffle furnace, and then the temperature is increased to 300-400°C at a heating rate of 5-10°C / min, and the temperature is kept for 3-5h, and finally the furnace is cooled to room temperature; the material of the clamping tooling is graphite.

[0016] In the present invention, graphite is selected as the material of the clamping tool. After removing the sizing agent, the ceramic fiber and the clamping tool can be directly placed in a deposition furnace as a whole. The deposition furnace is a high-temperature, acidic environment. Graphite has the characteristics of high temperature resistance and corrosion resistance. It will not be corroded in the deposition furnace and can withstand high temperatures.

[0017] In any of the above schemes, preferably, in step 2, the vacuum system is turned on to evacuate the vacuum degree in the deposition furnace to no more than 25 Pa and maintained for 1 hour. If the vacuum degree does not increase, it can be determined that the sealing of the deposition furnace is good.

[0018] In any of the above schemes, it is preferred that in step three, the vacuum degree in the deposition furnace is 1000-5000Pa, and the flow rate of argon gas introduced into the deposition furnace is 5-20L / min; the heating process of the ceramic fiber bundle, ceramic fiber plain fabric or ceramic fiber satin fabric is: heating to 500°C at a heating rate of 5-10°C / min, keeping warm for 10-30min, continuing to heating to 900-1300°C at a heating rate of 3-5°C / min, and keeping warm for 20-60min; the heating process of the ceramic fiber 2.5D fabric or ceramic fiber 3D fabric is: heating to 500°C at a heating rate of 5-10°C / min, keeping warm for 30-60min, continuing to heating to 600-800°C at a heating rate of 3-5°C / min, and keeping warm for 40-100min.

[0019] In any of the above schemes, it is preferred that in step four, the vacuum degree in the deposition furnace is reduced to no more than 25Pa.

[0020] In any of the above schemes, preferably, in step 5, H2 is first introduced into the deposition furnace, and the H2 flow rate is 10-100 L / min; after H2 is introduced for 5-10 minutes, NH3 is continuously introduced into the deposition furnace, and the NH3 flow rate is 10-100 L / min; after NH3 is introduced for 5-10 minutes, BCl3 is continuously introduced into the deposition furnace, and the ratio of the BCl3 flow rate to the NH3 flow rate is 1:5-10; after BCl3 is introduced for 2-5 minutes, TiCl4 is continuously introduced into the deposition furnace, The ratio of TiCl4 flow rate to NH3 flow rate is 1:3-9; after TiCl4 is introduced for 5-10 minutes, TiCl4 and SiCl4 are continuously introduced into the deposition furnace, and the ratio of TiCl4 flow rate to NH3 flow rate is 1:6-12, and the ratio of SiCl4 flow rate to NH3 flow rate is 1:6-12. At this time, five reaction gases, H2, NH3, BCl3, TiCl4 and SiCl4, are introduced into the deposition furnace at the same time, and the five reaction gases are chemically vapor deposited on the surface of the ceramic fiber.

[0021] In the present invention, TiCl4 and SiCl4 are originally liquid, TiCl4 and SiCl4 liquid are first converted into gas, and then TiCl4 and SiCl4 gas are introduced into the deposition furnace. TiCl4 liquid and SiCl4 liquid are stored in different liquid tanks, respectively, and nitrogen is introduced into the TiCl4 liquid tank and SiCl4 liquid tank respectively to increase the pressure in the liquid tank, and the liquid is squeezed into the gas tank, and then the gas tank is heated and kept warm to make the liquid in the gas tank evaporate continuously to form gas.

[0022] In any of the above schemes, it is preferred that in step five, the deposition temperature of the ceramic fiber bundle is 900-1300°C, the deposition pressure is 500-2000Pa, and the deposition time is 10-30min, the deposition temperature of the ceramic fiber plain fabric or the ceramic fiber satin fabric is 900-1300°C, the deposition pressure is 500-2000Pa, and the deposition time is 30-90min, and the deposition temperature of the ceramic fiber 2.5D fabric or the ceramic fiber 3D fabric is 600-800°C, the deposition pressure is 50-500Pa, and the deposition time is 120-600min.

[0023] In the present invention, H2 is first introduced into the deposition furnace with a flow rate of 10-100 L / min. Within 1 minute after the introduction of H2, the pressure in the deposition furnace reaches the deposition pressure.

[0024] In any of the above schemes, preferably, in step 6, the flow rate of argon gas introduced into the deposition furnace is 20-50 L / min, and the atmospheric pressure is 10 5 Pa.

[0025] The preparation method of the TiSiBN interface coating on the surface of ceramic fiber of the present invention uses the ceramic fiber commonly used in ceramic-based composite materials as a deposition substrate, uses TiCl4, SiCl4, BCl3 and NH3 as reaction precursors, and prepares the TiSiBN interface coating on the surface of the ceramic fiber through a chemical vapor infiltration deposition process. The method adopts a simple process, adjustable components, and high bonding strength between the ceramic fiber and the interface coating. By adding Ti elements and Si elements to BN, the prepared TiSiBN interface coating has excellent oxidation resistance and water and oxygen resistance. In the subsequent preparation process of the ceramic-based composite material, the TiSiBN interface coating can prevent air diffusion, protect the ceramic fiber from being affected by oxygen, prevent the interface between the ceramic matrix and the ceramic fiber from reacting, meet the requirements of the ceramic-based composite material for interface bonding, improve the service performance of the ceramic-based composite material in a water and oxygen environment, and realize the application range of the ceramic-based composite material in an actual use environment.

[0026] The method for preparing the TiSiBN interface coating on the surface of ceramic fibers of the present invention has the following beneficial effects:

[0027] (1) The BN interfacial coating containing Ti and Si elements was prepared by chemical vapor infiltration deposition process. During the deposition process, a chemical reaction occurred on the surface of the ceramic fiber, which not only formed a good bond with the ceramic fiber, but also Ti and Si existed in BN in a chemically bonded manner, and could also better bond with each other, thereby greatly improving its water and oxygen resistance.

[0028] (2) The introduction of Ti and Si elements into the BN interface can increase the corrosion resistance of the interface coating. In the subsequent preparation process of ceramic-based composites, it can increase the protection of ceramic fibers and maintain a high strength retention rate of ceramic fibers, thereby improving the mechanical properties of ceramic-based composites.

[0029] (3) TiSiBN interface coating is prepared by using TiCl4, SiCl4, BCl3 and NH3 as precursors. The intake ratio can be adjusted in real time to control the content of Ti and Si in the interface. According to the requirements of the interface coating for the preparation process of different substrates, the interface coating with suitable components can be selected, which has high designability.

[0030] (4) The structure of the prepared TiSiBN interface coating is uniform and dense, and the gas permeability and thickness can be regulated by controlling the process conditions. It can be used to prepare interface coatings on the surfaces of fibers of different types and fabric forms. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A flow chart of a preferred embodiment of a method for preparing a TiSiBN interface coating on a ceramic fiber surface according to the present invention;

[0032] Figure 2 for Figure 1 Photographs of TiSiBN interfacial coatings in the illustrated embodiments;

[0033] Figure 3 A photograph of a TiSiBN interface coating in another preferred embodiment of the method for preparing a TiSiBN interface coating on a ceramic fiber surface according to the present invention;

[0034] Figure 4 A photograph of a TiSiBN interface coating in another preferred embodiment of the method for preparing a TiSiBN interface coating on a ceramic fiber surface according to the present invention;

[0035] Figure 5 A photograph of a TiSiBN interface coating in another preferred embodiment of the method for preparing a TiSiBN interface coating on a ceramic fiber surface according to the present invention;

[0036] Figure 6 A photograph of a TiSiBN interface coating in another preferred embodiment of the method for preparing a TiSiBN interface coating on a ceramic fiber surface according to the present invention;

[0037] Figure 7 This is a photograph of a TiSiBN interfacial coating in another preferred embodiment of the method for preparing a TiSiBN interfacial coating on a ceramic fiber surface according to the present invention. DETAILED DESCRIPTION

[0038] In order to further understand the content of the present invention, the present invention will be described in detail below in conjunction with specific embodiments.

[0039] Embodiment 1:

[0040] like Figure 1 As shown, according to a preferred embodiment of the method for preparing the TiSiBN interface coating on the surface of ceramic fiber of the present invention, the following steps are included in order:

[0041] Step 1: Use a clamping tool to clamp the ceramic fiber and place it in a muffle furnace to remove the sizing agent;

[0042] Step 2: Place the ceramic fiber after the sizing agent is removed and the clamping tooling into the deposition chamber of the deposition furnace, and turn on the vacuum system to check the sealing of the deposition furnace;

[0043] Step 3: Turn on the vacuum system to evacuate the deposition furnace, and at the same time, introduce argon gas into the deposition furnace, and then turn on the heating system to heat it, and keep evacuating and introducing argon gas during the entire heating process;

[0044] Step 4: After the heating is completed, stop introducing argon gas and reduce the vacuum degree;

[0045] Step 5: Four reaction gases, H2, NH3, BCl3 and TiCl4, are introduced into the deposition furnace in sequence, and then two reaction gases, TiCl4 and SiCl4, are introduced into the deposition furnace at the same time, and the reaction gases are chemically vapor deposited on the surface of the ceramic fiber;

[0046] Step 6: After the chemical vapor deposition is completed, the gas channels of TiCl4, SiCl4, BCl3, NH3 and H2 are closed in turn, and then argon gas is introduced into the deposition furnace until the pressure in the deposition furnace reaches normal pressure. The heating system and the vacuum system are closed to obtain a TiSiBN interface coating on the surface of the ceramic fiber.

[0047] In step one, the ceramic fiber is silicon carbide fiber, and the type of the ceramic fiber is ceramic fiber plain fabric. The process of removing the sizing agent from the ceramic fiber plain fabric is as follows: first, the ceramic fiber plain fabric is placed in a muffle furnace, and then heated to 320°C at a heating rate of 8°C / min, kept warm for 1.2 hours, and finally cooled to room temperature with the furnace. The material of the clamping tool is graphite. In this embodiment, after removing the sizing agent, the ceramic fiber and the clamping tool can be directly placed in the deposition furnace as a whole. The deposition furnace is a high temperature and acidic environment. Graphite has the characteristics of high temperature resistance and corrosion resistance. It will not be corroded in the deposition furnace and can withstand high temperatures.

[0048] In step 2, the vacuum system is turned on to draw the vacuum degree in the deposition furnace to 25 Pa and maintained for 1 hour. If the vacuum degree does not increase, it can be determined that the sealing of the deposition furnace is good.

[0049] In step 3, the vacuum degree in the deposition furnace is 3000Pa, and the flow rate of argon gas into the deposition furnace is 12L / min. The heating process of the ceramic fiber plain fabric is: heating to 500°C at a heating rate of 8°C / min, keeping warm for 20min, and then heating to 1100°C at a heating rate of 4°C / min, keeping warm for 40min.

[0050] In step 4, the vacuum degree in the deposition furnace is reduced to 25Pa.

[0051] In step 5, H2 is first introduced into the deposition furnace, and the H2 flow rate is 50 L / min; after H2 is introduced for 8 minutes, NH3 is continuously introduced into the deposition furnace, and the NH3 flow rate is 50 L / min; after NH3 is introduced for 8 minutes, BCl3 is continuously introduced into the deposition furnace, and the ratio of the BCl3 flow rate to the NH3 flow rate is 1:8, that is, the BCl3 flow rate is 6.25 L / min; after BCl3 is introduced for 3.5 minutes, TiCl4 is continuously introduced into the deposition furnace, and the ratio of the TiCl4 flow rate to the NH3 flow rate is 1: 6, that is, the TiCl4 flow rate is 8.33L / min; after TiCl4 is introduced for 7.5min, TiCl4 and SiCl4 are continuously introduced into the deposition furnace, and the ratio of TiCl4 flow rate, SiCl4 flow rate and NH3 flow rate are all 1:9, that is, the TiCl4 flow rate and SiCl4 flow rate are both 5.56L / min, at this time, five reaction gases, H2, NH3, BCl3, TiCl4 and SiCl4, are introduced into the deposition furnace at the same time, and the five reaction gases are chemically vapor deposited on the surface of the ceramic fiber. The deposition temperature of the ceramic fiber plain weave fabric is 1100°C, the deposition pressure is 1200Pa, and the deposition time is 60min, which is the time for the five reaction gases to simultaneously perform chemical vapor deposition on the surface of the ceramic fiber.

[0052] In this embodiment, the pressure in the deposition furnace reaches the deposition pressure within 1 minute after H2 is introduced into the deposition furnace. TiCl4 and SiCl4 are originally liquids. TiCl4 and SiCl4 liquids are first converted into gases, and then TiCl4 and SiCl4 gases are introduced into the deposition furnace. TiCl4 liquid and SiCl4 liquid are stored in different liquid tanks, respectively. Nitrogen is introduced into the TiCl4 liquid tank and SiCl4 liquid tank, respectively, to increase the pressure in the liquid tank, squeeze the liquid into the gas tank, and then heat and keep the gas tank warm, so that the liquid in the gas tank evaporates continuously to form gas.

[0053] In step 6, the flow rate of argon gas into the deposition furnace is 35L / min, and the atmospheric pressure is 10 5 Pa.

[0054] The preparation method of the TiSiBN interface coating on the surface of the ceramic fiber of this embodiment uses the ceramic fiber commonly used in the ceramic-based composite material as the deposition substrate, and uses TiCl4, SiCl4, BCl3 and NH3 as reaction precursors to prepare the TiSiBN interface coating on the surface of the ceramic fiber through a chemical vapor infiltration deposition process. The process adopted by this method is simple, the components are adjustable, and the bonding strength between the ceramic fiber and the interface coating is high. By adding Ti and Si elements to BN, the prepared TiSiBN interface coating has excellent oxidation resistance and water oxygen resistance. In the subsequent preparation process of the ceramic-based composite material, the TiSiBN interface coating can prevent air diffusion, protect the ceramic fiber from the influence of oxygen, prevent the interface between the ceramic matrix and the ceramic fiber from reacting, meet the requirements of the ceramic-based composite material for the interface bonding degree, improve the service performance of the ceramic-based composite material in a water-oxygen environment, and realize the application range of the ceramic-based composite material in the actual use environment.

[0055] The preparation method of the TiSiBN interface coating on the surface of the ceramic fiber of this embodiment has the following beneficial effects: (1) The BN interface coating containing Ti and Si elements is prepared by chemical vapor infiltration deposition process. During the deposition process, a chemical reaction occurs on the surface of the ceramic fiber, which can not only form a good combination with the ceramic fiber, but also Ti and Si exist in the BN in a chemically bonded manner, and can also be better combined with each other, thereby greatly improving its water and oxygen resistance. (2) The introduction of Ti and Si elements into the BN interface can increase the corrosion resistance of the interface coating. In the subsequent preparation process of the ceramic matrix composite material, the protection of the ceramic fiber can be increased, and the high strength retention rate of the ceramic fiber can be maintained, thereby improving the mechanical properties of the ceramic matrix composite material. (3) The TiSiBN interface coating is prepared by using TiCl4, SiCl4, BCl3 and NH3 as precursors, and the air intake ratio can be adjusted in real time to control the content of Ti and Si in the interface. According to the requirements of the preparation process of different substrates for the interface coating, the interface coating with suitable components can be selected, which has high designability. (4) The structure of the prepared TiSiBN interface coating is uniform and dense, and the gas permeability and thickness can be regulated by controlling the process conditions. It can be used to prepare interface coatings on the surfaces of fibers of different types and fabric forms.

[0056] Embodiment 2:

[0057] According to another preferred embodiment of the method for preparing the TiSiBN interface coating on the surface of ceramic fiber of the present invention, the process steps, the equipment used, the technical principle and the beneficial effects are basically the same as those of the first embodiment, except that:

[0058] In step 1, the ceramic fiber is silicon carbide fiber, and the type of the ceramic fiber is ceramic fiber satin fabric. The process for removing the sizing agent from the ceramic fiber satin fabric is as follows: firstly, the ceramic fiber satin fabric is placed in a muffle furnace, and then heated to 400°C at a heating rate of 10°C / min, kept at this temperature for 2 hours, and finally cooled to room temperature along with the furnace.

[0059] In step 2, the vacuum system is turned on to draw the vacuum degree in the deposition furnace to 25 Pa and maintained for 1 hour. If the vacuum degree does not increase, it can be determined that the sealing of the deposition furnace is good.

[0060] In step 3, the vacuum degree in the deposition furnace is 2000Pa, and the flow rate of argon gas into the deposition furnace is 8L / min. The heating process of the ceramic fiber satin fabric is: heating to 500°C at a heating rate of 10°C / min, keeping warm for 30min, and then heating to 1300°C at a heating rate of 5°C / min, keeping warm for 60min.

[0061] In step 4, the vacuum degree in the deposition furnace is reduced to 25Pa.

[0062] In step 5, H2 was first introduced into the deposition furnace, and the H2 flow rate was 30 L / min. After H2 was introduced for 7 minutes, NH3 was continuously introduced into the deposition furnace, and the NH3 flow rate was 30 L / min. After NH3 was introduced for 7 minutes, BCl3 was continuously introduced into the deposition furnace, and the ratio of the BCl3 flow rate to the NH3 flow rate was 1:7, that is, the BCl3 flow rate was 4.29 L / min. After BCl3 was introduced for 2.8 minutes, TiCl4 was continuously introduced into the deposition furnace, and the ratio of the TiCl4 flow rate to the NH3 flow rate was 1:4, that is, the flow rate of TiCl4 is 7.5L / min; after TiCl4 is introduced for 6 minutes, TiCl4 and SiCl4 are continuously introduced into the deposition furnace, and the ratio of the flow rate of TiCl4, the flow rate of SiCl4 and the flow rate of NH3 is 1:8, that is, the flow rate of TiCl4 and the flow rate of SiCl4 are both 3.75L / min, at this time, five reaction gases of H2, NH3, BCl3, TiCl4 and SiCl4 are introduced into the deposition furnace at the same time, and the five reaction gases are chemically vapor deposited on the surface of the ceramic fiber. The deposition temperature of the ceramic fiber satin fabric is 1300°C, the deposition pressure is 2000Pa, and the deposition time is 90min, which is the time for the five reaction gases to simultaneously perform chemical vapor deposition on the surface of the ceramic fiber.

[0063] In step 6, the flow rate of argon gas into the deposition furnace is 50 L / min, and the atmospheric pressure is 10 5 Pa.

[0064] Embodiment three:

[0065] According to another preferred embodiment of the method for preparing the TiSiBN interface coating on the surface of ceramic fiber of the present invention, the process steps, the equipment used, the technical principle and the beneficial effects are basically the same as those of the first embodiment, except that:

[0066] In step 1, the ceramic fiber is silicon carbide fiber, and the type of the ceramic fiber is ceramic fiber bundle. The process of removing the sizing agent from the ceramic fiber bundle is: firstly, the ceramic fiber bundle is placed in a muffle furnace, and then heated to 250°C at a heating rate of 5°C / min, kept at this temperature for 0.5h, and finally cooled to room temperature with the furnace.

[0067] In step 2, the vacuum system is turned on to draw the vacuum degree in the deposition furnace to 25 Pa and maintained for 1 hour. If the vacuum degree does not increase, it can be determined that the sealing of the deposition furnace is good.

[0068] In step 3, the vacuum degree in the deposition furnace is 1000Pa, and the flow rate of argon gas into the deposition furnace is 5L / min. The heating process of the ceramic fiber bundle is: heating to 500°C at a heating rate of 5°C / min, keeping warm for 10 minutes, and then heating to 900°C at a heating rate of 3°C / min, keeping warm for 20 minutes.

[0069] In step 4, the vacuum degree in the deposition furnace is reduced to 25Pa.

[0070] In step 5, H2 is first introduced into the deposition furnace, and the H2 flow rate is 10 L / min; after H2 is introduced for 5 minutes, NH3 is continuously introduced into the deposition furnace, and the NH3 flow rate is 10 L / min; after NH3 is introduced for 5 minutes, BCl3 is continuously introduced into the deposition furnace, and the ratio of the BCl3 flow rate to the NH3 flow rate is 1:5, that is, the BCl3 flow rate is 2 L / min; after BCl3 is introduced for 2 minutes, TiCl4 is continuously introduced into the deposition furnace, and the ratio of the TiCl4 flow rate to the NH3 flow rate is 1:3 , that is, the TiCl4 flow rate is 3.33L / min; after TiCl4 is introduced for 5 minutes, TiCl4 and SiCl4 are continuously introduced into the deposition furnace, and the ratio of TiCl4 flow rate, SiCl4 flow rate and NH3 flow rate are all 1:6, that is, the TiCl4 flow rate and SiCl4 flow rate are both 1.67L / min, and at this time, five reaction gases, H2, NH3, BCl3, TiCl4 and SiCl4, are introduced into the deposition furnace at the same time, and the five reaction gases are chemically vapor deposited on the surface of the ceramic fiber. The deposition temperature of the ceramic fiber bundle is 900°C, the deposition pressure is 500Pa, and the deposition time is 30min, which is the time for the five reaction gases to simultaneously perform chemical vapor deposition on the surface of the ceramic fiber.

[0071] In step 6, the flow rate of argon gas into the deposition furnace is 20L / min, and the atmospheric pressure is 10 5 Pa.

[0072] Embodiment 4:

[0073] According to another preferred embodiment of the method for preparing the TiSiBN interface coating on the surface of ceramic fiber of the present invention, the process steps, the equipment used, the technical principle and the beneficial effects are basically the same as those of the first embodiment, except that:

[0074] In step 1, the ceramic fiber is silicon carbide fiber, and the type of the ceramic fiber is ceramic fiber 2.5D fabric. The process of removing the sizing agent from the ceramic fiber 2.5D fabric is as follows: firstly, the ceramic fiber 2.5D fabric is placed in a muffle furnace, and then heated to 300°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, and finally cooled to room temperature with the furnace.

[0075] In step 2, the vacuum system is turned on to draw the vacuum degree in the deposition furnace to 25 Pa and maintained for 1 hour. If the vacuum degree does not increase, it can be determined that the sealing of the deposition furnace is good.

[0076] In step 3, the vacuum degree in the deposition furnace is 4000Pa, and the flow rate of argon gas into the deposition furnace is 16L / min. The heating process of the ceramic fiber 2.5D fabric is: heating to 500°C at a heating rate of 5°C / min, keeping warm for 30 minutes, and then heating to 600°C at a heating rate of 3°C / min, keeping warm for 40 minutes.

[0077] In step 4, the vacuum degree in the deposition furnace is reduced to 25Pa.

[0078] In step 5, H2 was first introduced into the deposition furnace, and the H2 flow rate was 80 L / min; after H2 was introduced for 9 minutes, NH3 was continuously introduced into the deposition furnace, and the NH3 flow rate was 80 L / min; after NH3 was introduced for 9 minutes, BCl3 was continuously introduced into the deposition furnace, and the ratio of the BCl3 flow rate to the NH3 flow rate was 1:9, that is, the BCl3 flow rate was 8.89 L / min; after BCl3 was introduced for 4.2 minutes, TiCl4 was continuously introduced into the deposition furnace, and the ratio of the TiCl4 flow rate to the NH3 flow rate was 1:8, that is, the TiCl4 flow rate is 10L / min; after TiCl4 is introduced for 9 minutes, TiCl4 and SiCl4 are continuously introduced into the deposition furnace, and the ratio of TiCl4 flow rate, SiCl4 flow rate and NH3 flow rate is 1:11, that is, the TiCl4 flow rate and SiCl4 flow rate are both 7.27L / min, and at this time, five reaction gases, H2, NH3, BCl3, TiCl4 and SiCl4, are introduced into the deposition furnace at the same time, and the five reaction gases are chemically vapor deposited on the surface of the ceramic fiber. The deposition temperature of the ceramic fiber 2.5D fabric is 600°C, the deposition pressure is 50Pa, and the deposition time is 120min, which is the time for the five reaction gases to simultaneously perform chemical vapor deposition on the surface of the ceramic fiber.

[0079] In step 6, the flow rate of argon gas into the deposition furnace is 30L / min, and the atmospheric pressure is 10 5 Pa.

[0080] Embodiment five:

[0081] According to another preferred embodiment of the method for preparing the TiSiBN interface coating on the surface of ceramic fiber of the present invention, the process steps, the equipment used, the technical principle and the beneficial effects are basically the same as those of the first embodiment, except that:

[0082] In step 1, the ceramic fiber is silicon carbide fiber, and the type of the ceramic fiber is ceramic fiber 2.5D fabric. The process of removing the sizing agent from the ceramic fiber 2.5D fabric is as follows: firstly, the ceramic fiber 2.5D fabric is placed in a muffle furnace, and then heated to 350°C at a heating rate of 8°C / min, kept at this temperature for 4 hours, and finally cooled to room temperature with the furnace.

[0083] In step 2, the vacuum system is turned on to draw the vacuum degree in the deposition furnace to 25 Pa and maintained for 1 hour. If the vacuum degree does not increase, it can be determined that the sealing of the deposition furnace is good.

[0084] In step 3, the vacuum degree in the deposition furnace is 4500Pa, and the flow rate of argon gas into the deposition furnace is 18L / min. The heating process of the ceramic fiber 2.5D fabric is: heating to 500°C at a heating rate of 8°C / min, keeping warm for 45 minutes, and then heating to 700°C at a heating rate of 4°C / min, keeping warm for 70 minutes.

[0085] In step 4, the vacuum degree in the deposition furnace is reduced to 25Pa.

[0086] In step 5, H2 is first introduced into the deposition furnace, and the H2 flow rate is 80 L / min; after H2 is introduced for 8 minutes, NH3 is continuously introduced into the deposition furnace, and the NH3 flow rate is 80 L / min; after NH3 is introduced for 8 minutes, BCl3 is continuously introduced into the deposition furnace, and the ratio of the BCl3 flow rate to the NH3 flow rate is 1:8, that is, the BCl3 flow rate is 10 L / min; after BCl3 is introduced for 4 minutes, TiCl4 is continuously introduced into the deposition furnace, and the ratio of the TiCl4 flow rate to the NH3 flow rate is 1 :8, that is, the TiCl4 flow rate is 10L / min; after TiCl4 is introduced for 8 minutes, TiCl4 and SiCl4 are continuously introduced into the deposition furnace, and the ratio of TiCl4 flow rate, SiCl4 flow rate and NH3 flow rate is 1:10, that is, the TiCl4 flow rate and SiCl4 flow rate are both 8L / min, and at this time, five reaction gases, H2, NH3, BCl3, TiCl4 and SiCl4, are introduced into the deposition furnace at the same time, and the five reaction gases are chemically vapor deposited on the surface of the ceramic fiber. The deposition temperature of the ceramic fiber 2.5D fabric is 700°C, the deposition pressure is 250Pa, and the deposition time is 360min, which is the time for the five reaction gases to simultaneously perform chemical vapor deposition on the surface of the ceramic fiber.

[0087] In step 6, the flow rate of argon gas into the deposition furnace is 30L / min, and the atmospheric pressure is 10 5 Pa.

[0088] Embodiment six:

[0089] According to another preferred embodiment of the method for preparing the TiSiBN interface coating on the surface of ceramic fiber of the present invention, the process steps, the equipment used, the technical principle and the beneficial effects are basically the same as those of the first embodiment, except that:

[0090] In step 1, the ceramic fiber is silicon carbide fiber, and the type of the ceramic fiber is ceramic fiber 3D fabric. The process of removing the sizing agent from the ceramic fiber 3D fabric is as follows: firstly, the ceramic fiber 3D fabric is placed in a muffle furnace, and then heated to 400°C at a heating rate of 10°C / min, kept at this temperature for 5 hours, and finally cooled to room temperature with the furnace.

[0091] In step 2, the vacuum system is turned on to draw the vacuum degree in the deposition furnace to 25 Pa and maintained for 1 hour. If the vacuum degree does not increase, it can be determined that the sealing of the deposition furnace is good.

[0092] In step 3, the vacuum degree in the deposition furnace is 5000Pa, and the flow rate of argon gas into the deposition furnace is 20L / min. The heating process of the ceramic fiber 3D fabric is: heating to 500°C at a heating rate of 10°C / min, keeping warm for 60 minutes, and then heating to 800°C at a heating rate of 5°C / min, keeping warm for 100 minutes.

[0093] In step 4, the vacuum degree in the deposition furnace is reduced to 25Pa.

[0094] In step 5, H2 is first introduced into the deposition furnace, and the H2 flow rate is 100 L / min; after H2 is introduced for 10 minutes, NH3 is continuously introduced into the deposition furnace, and the NH3 flow rate is 100 L / min; after NH3 is introduced for 10 minutes, BCl3 is continuously introduced into the deposition furnace, and the ratio of the BCl3 flow rate to the NH3 flow rate is 1:10, that is, the BCl3 flow rate is 10 L / min; after BCl3 is introduced for 5 minutes, TiCl4 is continuously introduced into the deposition furnace, and the ratio of the TiCl4 flow rate to the NH3 flow rate is 1: 9, that is, the TiCl4 flow rate is 11.11L / min; after TiCl4 is introduced for 10 minutes, TiCl4 and SiCl4 are continuously introduced into the deposition furnace, and the ratio of TiCl4 flow rate, SiCl4 flow rate and NH3 flow rate is 1:12, that is, the TiCl4 flow rate and SiCl4 flow rate are both 8.33L / min, and at this time, five reaction gases, H2, NH3, BCl3, TiCl4 and SiCl4, are introduced into the deposition furnace at the same time, and the five reaction gases are chemically vapor deposited on the surface of the ceramic fiber. The deposition temperature of the ceramic fiber 2.5D fabric is 800°C, the deposition pressure is 500Pa, and the deposition time is 600min, which is the time for the five reaction gases to simultaneously perform chemical vapor deposition on the surface of the ceramic fiber.

[0095] In step 6, the flow rate of argon gas into the deposition furnace is 30L / min, and the atmospheric pressure is 10 5 Pa.

[0096] Figure 2-7 The scanning electron microscope photos of the TiSiBN interface coating prepared in the above-mentioned embodiments 1 to 6 are respectively. Performance test experiments were carried out for the above-mentioned embodiments 1 to 6, and the test data are shown in Tables 1-4, wherein Tables 1 and 2 are respectively the mechanical property test results of the SiC fiber before and after the TiSiBN interface coating is deposited in the embodiments 1 to 6, and Tables 3 and 4 are respectively the mechanical property test results of the SiC fiber after water-oxygen treatment before and after the TiSiBN interface coating is deposited in the embodiments 1 to 6.

[0097] Table 1 Mechanical properties test results of SiC fibers before deposition of TiSiBN interfacial coating

[0098] Test No. Fiber diameter (μm) Tensile strength(GPa) Embodiment 1 12.24 2.88 Embodiment 2 11.94 2.94 Embodiment 3 12.05 2.79 Embodiment 4 12.34 3.04 Embodiment 5 11.84 3.10 Embodiment 6 12.09 2.74

[0099] Table 2 Mechanical properties test results of SiC fibers after deposition of TiSiBN interfacial coating

[0100] Test No. Interface coating thickness (μm) Fiber diameter (μm) Tensile strength(GPa) Strength retention rate (%) Embodiment 1 1.27 14.78 2.44 84.72 Embodiment 2 1.45 14.84 2.51 85.37 Embodiment 3 0.57 13.19 2.53 90.68 Embodiment 4 0.61 13.56 2.79 91.77 Embodiment 5 0.85 13.52 2.75 88.71 Embodiment 6 1.41 14.91 2.40 87.59

[0101] Table 3 Mechanical properties test results of SiC fibers after water-oxygen treatment before deposition of TiSiBN interfacial coating

[0102]

[0103] Table 4 Mechanical properties test results of SiC fibers after water-oxygen treatment after deposition of TiSiBN interfacial coating

[0104]

[0105] from Figure 2-7 As can be seen from Tables 1-4, the BN interface coating containing Ti and Si elements prepared by chemical vapor infiltration deposition process undergoes chemical reaction on the surface of ceramic fiber during the deposition process, which not only forms a good bond with ceramic fiber, but also Ti and Si exist in BN in a chemically bonded manner and can better bond with each other. The introduction of Ti and Si elements into the BN interface increases the protection of ceramic fiber and maintains a high strength retention rate of ceramic fiber.

[0106] Special note: The technical solution of the present invention involves many parameters, and the synergistic effects between the various parameters need to be comprehensively considered to obtain the beneficial effects and significant progress of the present invention. Moreover, the value ranges of the various parameters in the technical solution are obtained after a large number of experiments. For each parameter and the combination of each parameter, the inventor has recorded a large amount of experimental data. Due to space limitations, the specific experimental data will not be disclosed here.

[0107] It is not difficult for a person skilled in the art to understand that the method for preparing the TiSiBN interface coating on the surface of the ceramic fiber of the present invention includes any combination of the invention content and the specific implementation method of the above-mentioned invention specification and the various parts shown in the drawings. Due to the limited space and to make the specification concise, the various schemes composed of these combinations are not described one by one. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a TiSiBN interface coating on a ceramic fiber surface, comprising the following steps in chronological order: Step 1: Use a clamping tool to clamp the ceramic fiber and place it in a muffle furnace to remove the sizing agent; Step 2: Place the ceramic fiber after the sizing agent is removed and the clamping tooling into the deposition chamber of the deposition furnace, and turn on the vacuum system to check the sealing of the deposition furnace; Step 3: Turn on the vacuum system to evacuate the deposition furnace, and at the same time, introduce argon gas into the deposition furnace, and then turn on the heating system to heat it, and keep evacuating and introducing argon gas during the entire heating process; Step 4: After the heating is completed, stop introducing argon gas and reduce the vacuum degree; Step 5: Four reaction gases, H2, NH3, BCl3 and TiCl4, are introduced into the deposition furnace in sequence, and then two reaction gases, TiCl4 and SiCl4, are introduced into the deposition furnace at the same time, and the reaction gases are chemically vapor deposited on the surface of the ceramic fiber; Step 6: After the chemical vapor deposition is completed, the gas channels of TiCl4, SiCl4, BCl3, NH3 and H2 are closed in sequence, and then argon gas is introduced into the deposition furnace until the pressure in the deposition furnace is normal pressure, and the heating system and the vacuum system are closed to obtain a TiSiBN interface coating on the surface of the ceramic fiber; The type of the ceramic fiber is any one of ceramic fiber bundle yarn, ceramic fiber plain fabric, ceramic fiber satin fabric, ceramic fiber 2.5D fabric or ceramic fiber 3D fabric; In step 1, the process for removing the sizing agent from the ceramic fiber bundle, ceramic fiber plain fabric or ceramic fiber satin fabric is to first place the ceramic fiber bundle, ceramic fiber plain fabric or ceramic fiber satin fabric in a muffle furnace, and then heat it to 250-400°C at a heating rate of 5-10°C / min, keep it warm for 0.5-2h, and finally cool it to room temperature with the furnace; the process for removing the sizing agent from the ceramic fiber 2.5D fabric or ceramic fiber 3D fabric is to first place the ceramic fiber 2.5D fabric or ceramic fiber 3D fabric in a muffle furnace, and then heat it to 300-400°C at a heating rate of 5-10°C / min, keep it warm for 3-5h, and finally cool it to room temperature with the furnace; In step three, the heating process of the ceramic fiber bundle, ceramic fiber plain fabric or ceramic fiber satin fabric is to heat up to 500°C at a heating rate of 5-10°C / min, keep warm for 10-30min, continue to heat up to 900-1300°C at a heating rate of 3-5°C / min, and keep warm for 20-60min; the heating process of the ceramic fiber 2.5D fabric or ceramic fiber 3D fabric is to heat up to 500°C at a heating rate of 5-10°C / min, keep warm for 30-60min, continue to heat up to 600-800°C at a heating rate of 3-5°C / min, and keep warm for 40-100min; In step 5, H2 is first introduced into the deposition furnace, and the H2 flow rate is 10-100 L / min; after H2 is introduced for 5-10 minutes, NH3 is continuously introduced into the deposition furnace, and the NH3 flow rate is 10-100 L / min; after NH3 is introduced for 5-10 minutes, BCl3 is continuously introduced into the deposition furnace, and the ratio of the BCl3 flow rate to the NH3 flow rate is 1:5-10; after BCl3 is introduced for 2-5 minutes, TiCl4 is continuously introduced into the deposition furnace, and the TiCl4 flow rate is 1:

10. The ratio of the flow rate of TiCl4 to the flow rate of NH3 is 1:3-9; after TiCl4 is introduced for 5-10 minutes, TiCl4 and SiCl4 are continuously introduced into the deposition furnace, the ratio of the flow rate of TiCl4 to the flow rate of NH3 is 1:6-12, and the ratio of the flow rate of SiCl4 to the flow rate of NH3 is 1:6-12. At this time, five reaction gases, H2, NH3, BCl3, TiCl4 and SiCl4, are introduced into the deposition furnace at the same time, and the five reaction gases are chemically vapor deposited on the surface of the ceramic fiber; In step five, the deposition temperature of the ceramic fiber bundle is 900-1300°C, the deposition pressure is 500-2000Pa, and the deposition time is 10-30min. The deposition temperature of the ceramic fiber plain fabric or ceramic fiber satin fabric is 900-1300°C, the deposition pressure is 500-2000Pa, and the deposition time is 30-90min. The deposition temperature of the ceramic fiber 2.5D fabric or ceramic fiber 3D fabric is 600-800°C, the deposition pressure is 50-500Pa, and the deposition time is 120-600min.

2. The method for preparing the TiSiBN interface coating on the surface of ceramic fiber according to claim 1, characterized in that: The ceramic fiber is any one of carbon fiber, silicon carbide fiber, boron nitride fiber or silicon nitride fiber.

3. The method for preparing the TiSiBN interface coating on the surface of ceramic fiber according to claim 2, characterized in that: In step 1, the material of the clamping tool is graphite.

4. The method for preparing the TiSiBN interface coating on the surface of ceramic fiber according to claim 3, characterized in that: In step 2, the vacuum system is turned on to evacuate the vacuum degree in the deposition furnace to no more than 25 Pa and maintained for 1 hour. If the vacuum degree does not increase, it can be determined that the sealing of the deposition furnace is good.

5. The method for preparing the TiSiBN interface coating on the surface of ceramic fiber according to claim 4, characterized in that: In step three, the vacuum degree in the deposition furnace is 1000-5000 Pa, and the flow rate of argon gas introduced into the deposition furnace is 5-20 L / min.

6. The method for preparing the TiSiBN interface coating on the surface of ceramic fiber according to claim 5, characterized in that: In step 4, the vacuum degree in the deposition furnace is reduced to no more than 25Pa.

7. The method for preparing the TiSiBN interface coating on the surface of ceramic fiber according to claim 6, characterized in that: In step 6, the flow rate of argon gas into the deposition furnace is 20-50 L / min, and the atmospheric pressure is 10 5 Pa.

Citation Information

Patent Citations

  • Preparation method of wave-transparent ceramic-base composite material containing silicon-boron-nitrogen interface

    CN108892521A